THE RESULTS OF THE BANK'S HEALTH ASSESSMENT ARE BASED ON A RISK PROFILE, GOOD CORPORATE GOVERNANCE, EARNINGS, AND CAPITAL (RGEC) AT PT. BANK BANTEN TBK - Leni Triana; Yuliah Yuliah; Ihda Nadiyah (SEAN Institute, 2023)
Banks are systematic institutions, meaning that the fall of one system in a bank will affect the stability of the financial system and public confidence in baking. The purpose of this study was to determine how the level of bank soundness at PT. Bank Banten, Tbk using the RGEC method for the 2017-2021 period. The research method used is qualitative, namely information data from verbal sentences or secondary data. Data obtained from PT. Bank Banten, Tbk was tested through financial ratios and bank health analysis. The results of the research on the bank's soundness level at PT. Bank Banten, Tbk for the period 2017-2021 experienced a significant situation and experienced an increase and decrease. When viewed from the Risk Profile factor component using financial ratios Non Performing Loan (NPL) is categorized as relatively healthy. The Loan Deposit Ratio (LDR) is categorized as relatively healthy, judging from the component of the Good Corporate Governance (GCG) factor, as quite healty, seen from the Earning factor component using the Return On Assets (ROA) financial ratio as very healty , judging from the Net Interest Margin (NIM) factor component is categorized as relatively healthy, viewed from the Capital factor component using the Capital Adequcy Ratio (CAR) financial ratio, as healthy. Based on the results of research done at the banking company PT. Bank Banten, Tbk stated that the soundnees level of the banking company received the predicate of very healthy financial condition, and not healthy. Overall 2017, 2018, 2019, 2021, is at PK-3 (reasonably healthy) and in 2020 it is at PK-4 (unhealthy).